Effectiveness of the personal hygiene module in increasing the knowledge of pregnant women with anemia on the dangers of worm infection - Saraswati, Endah; Wahida, Wahida; Nurdjaya, Malahayati (Universitas Muhammadiyah Purwokerto, 2025)
Background: Worm infections are a common cause of anemia in pregnant women, particularly in areas with poor sanitation. While many studies have examined anemia in pregnancy, few have specifically explored the effectiveness of personal hygiene education in increasing pregnant women's knowledge of the dangers of worm infection.Purpose: Â This study aimed to evaluate the effectiveness of a personal hygiene module in increasing the knowledge of pregnant women with anemia about the dangers of worm infection. Methods: This quasi-experimental study, which involved 30 pregnant women with anemia, was conducted in the coastal area of North Konawe Regency, Southeast Sulawesi Province. A purposive sampling technique was used, and data were analyzed using the paired t-test.Result: The average knowledge score before education was 29.27, significantly increasing to 52.40 after implementing the personal hygiene module (p = 0.000).Conclusions: The personal hygiene module effectively improves the knowledge of pregnant women with anemia regarding the dangers of worm infection.